Statistical Yearbook 2005, Fiftieth Issue - United Nations Department of Economic; Social Affairs (United Nations, 2006)
The Statistical Yearbook is an annual compilation of a wide range of international economic, social and environmental statistics on over 200 countries and areas, compiled from sources including UN agencies and other international, national and specialized organizations. The 50th issue contains data available to the Statistics Division as of March 2006 and presents them in 76 tables. The number of years of data shown in the tables varies from one to ten, with the ten-year tables covering 1994 to 2003 or 1995 to 2004. Accompanying the tables are technical notes providing brief descriptions of major statistical concepts, definitions and classifications.